The Role of Good Promise School Volunteers in Supporting SDGs 4 for Underprivileged Children - Octavina, Triansani; Rosmilawati, Ila; Siregar, Herlina (Journal of Nonformal Education and Community Empowerment, 2024)
"Sekolah Janji Baik" is one of the non-profit organizations that provides free education to underprivileged communities through volunteerism. This research aims to identify the role of Janji Baik school's volunteerism as a non-formal educational institution and to build Sustainable Development Goals (SDGs) pillar 4. The research used a qualitative descriptive method conducted from September 2023 to February 2024. Data collection techniques included observation, interviews, and documentation. Data validity was ensured through technique triangulation and source triangulation. Data analysis followed three stages: data reduction, data presentation, and conclusion drawing. The research results indicate that Janji Baik school volunteers have roles in a) administrative tasks, handling student files until they are registered in the Education Data Registry; b) work service, preparing learning facilities and infrastructure; c) teaching, conducting both academic and non-academic teaching; d) fundraising, raising funds to support learning programs. Janji Baik school also provides adequate access to education, evaluates learning activities to enhance teaching and learning quality, and provides educational facilities preparing students for the future, thereby contributing to the realization of SDGs pillar 4.